Investigating the Reading Preferences of Young Female Readers of Hausa Popular Prose Fiction: A Feminist Approach - Haruna Alkasim Kiyawa (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2018)
Reading the story of popular romance fiction is the most powerful social activities among women in the Western countries, Europe, Asia and Africa for their leisure and enjoyment. In this study an attempt has been made to understand the reading habits and preferences of the young adult female readers of Hausa popular romance fiction, the contemporary romance fiction are popular because it deals with unimaginable relationship between men and female, the novels help them to solve some issues on courtship, ineqality, domestic violence and social change. In this study a face to face interviews was employed to collect their views, feelings and understanding of 10 young female readers through the Rosenblatt’s Reader-response theory (1978). The data were analyzed using the constant comparative method. The findings of the study indicated four main outcomes which revealed the major motivating factors which includes; (i ) image of flashy car appeared at the cover page (ii) image of beautiful flowers, (iii)  image of golden ring (iv) Heart images, this images played a significant role for encouraging the readers to select a novel and read the story enjoy the freedom from breaking free of gender constraints through those stories consider it as part of their lives.